Effects of athletic and coaching experience on coaching efficacy in team sports - Meletakos, P.a; Bayios, I.a; Hatziharistos, D.b; Psychountaki, M.b (Gazzetta Medica Italiana Archivio per le Scienze Mediche, 2013)
Aim: The aim of the present study was to investigate the effects of the coach’s coaching and athletic experience on the four dimensions of Coaching Efficacy Scale (CES). Methods: The initial sample comprised 289 Greek male coaches, aged 39-6+6.9 years, from five different team sports (basketball, volleyball, football, handball, waterpolo). Combining the coaches’ high or low level of athletic and coaching experience, they were divided into four levels of experience profile. All coaches answered the Greek version of the 24-item questionnaire of Coaching Efficacy Scale during the final stages of the competition year of 2008-2009. Results: The MANOVA model revealed a significant effect of coaching and athletic experience on the dimensions of motivation, strategy and technique. Motivation is influenced only by athletic experience, while the presence of either coaching or athletic experience is sufficient to improve the efficacy of strategy. Conversely, the efficacy of technique can be significantly improved only if the coach has both adequate coaching and athletic experience. Finally the dimension of character building is not influenced by either the coaching or athletic experience. Conclusion: In conclusion, the three dimensions of CES (motivation, strategy and technique) are moderated by the coaches’ experience profile, with coaching and athletic experience acting specifically on each of the three dimensions.
Keywords: Adult; article; athletic trainer; basketball; character; football; human; major clinical study; Male; motivation; questionnaire; rating scale; sport; strategic planning; training; volleyball; work experience